Предмет: Алгебра,
автор: kaneky
преобразовать в многочлен
(a+b)(c+d)=
(a+2)(b-c)=
(a-1)(a+b-2)=
(a-b)(a+b)=
(a+b(a+b)=
Ответы
Автор ответа:
1
(a+b)(c+d)= ac + ad + bc + bd
(a+2)(b-c)= ab - ac + 2b - 2c
(a-1)(a+b-2)=a^2 + ab - 2a - a - b + 2 = a^2 + ab - 3a - b + 2
(a-b)(a+b)= a^2 - b^2
(a+b(a+b)= ( a + b )^2 = a^2 + 2ab + b^2
(a+2)(b-c)= ab - ac + 2b - 2c
(a-1)(a+b-2)=a^2 + ab - 2a - a - b + 2 = a^2 + ab - 3a - b + 2
(a-b)(a+b)= a^2 - b^2
(a+b(a+b)= ( a + b )^2 = a^2 + 2ab + b^2
Похожие вопросы
Предмет: Математика,
автор: odaanet335
Предмет: Английский язык,
автор: anytochkaa02
Предмет: Английский язык,
автор: sonaavdonina356
Предмет: История,
автор: lizaglazkova448